2017
DOI: 10.3389/fped.2017.00012
|View full text |Cite
|
Sign up to set email alerts
|

Venous Thromboembolism in Children with Cancer and Blood Disorders

Abstract: Venous thromboembolism (VTE) in children is multifactorial and most often related to a combination of inherited and acquired thrombophilias. Children with cancer and blood disorders are often at risk for VTE due to disease-related factors such as inflammation and abnormal blood flow and treatment-related factors such as central venous catheters and surgery. We will review risk factors for VTE in children with leukemia, lymphoma, and solid tumors. We will also review risk factors for VTE in children with blood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
1
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 92 publications
2
15
1
5
Order By: Relevance
“…Akin to the reported literature on VTE in patients with sarcoma, it may be that in our study the increased requirement of tPA seen in sarcoma patients is a reflection of the increased incidence of VTE formation …”
Section: Discussionsupporting
confidence: 56%
“…Akin to the reported literature on VTE in patients with sarcoma, it may be that in our study the increased requirement of tPA seen in sarcoma patients is a reflection of the increased incidence of VTE formation …”
Section: Discussionsupporting
confidence: 56%
“…Numerous studies have demonstrated an increased rate of VTE in pediatric patients with malignancy. 70,71 Pediatric patients with malignancy can develop severe COVID-19. Current registry data do not show a significantly increased risk for severe infection, and VTE risk is not well studied in this population 72 ; however, a recent study in children shows that malignancy was a risk factor for thrombosis with COVID-19.…”
Section: 41mentioning
confidence: 99%
“…This patient's VTE risks include the diagnosis of active malignancy, central line, and recent asparaginase treatment. Numerous studies have demonstrated an increased rate of VTE in pediatric patients with malignancy 70,71 . Pediatric patients with malignancy can develop severe COVID‐19.…”
Section: Clinical Vignettesmentioning
confidence: 99%
“…Paediatric oncologic patients are at high risk of VTE due to disease and treatment-related factors, e.g., chemotherapy (asparaginase, steroids), CVC use and surgery [ 42 ]. The occurrence of VTE depends on the type of cancer, and acute lymphoblastic leukemia (ALL) is the most common malignancy associated with thrombosis in children (3–14%) [ 43 , 44 , 45 , 46 ].…”
Section: Risk Factorsmentioning
confidence: 99%